Rapid Antidepressant Activity of Ethanol Extract of Gardenia jasminoides Ellis Is Associated with Upregulation of BDNF Expression in the Hippocampus - Zhang, Hailou (Evid Based Complement Alternat Med, 2015)
Ethanol extract of Yueju pill, a Traditional Chinese Medicine herbal formula widely used to treat mood disorders, demonstrates rapid antidepressant effects similar to ketamine, likely via instant enhancement of brain-derived neurotrophic factor (BDNF) expression in the hippocampus. Here we investigated ethanol extracts of the constituent herbs of Yueju responsible for rapid antidepressant effects. Screening with tail suspension test in Kunming mice at 24 hours after a single administration of five individual constituent herbs of Yueju, we found that only Gardenia jasminoides Ellis (GJ) showed a significant effect. The antidepressant response started at 2 hours after GJ administration. Similar to Yueju and ketamine, a single administration of GJ significantly reduced the number of escape failures in the learned helplessness test. Furthermore, GJ decreased latency of food consumption in the novelty suppressed-feeding test. Additionally, starting from 2 hours and continuing for over 20 hours after GJ administration, BDNF expression in the hippocampus was upregulated, temporally linked with the antidepressant response. These findings suggest that GJ has rapid antidepressant effects, which are associated with the elevated expression of BDNF in the hippocampus. In Yueju formula, Yue represents GJ, as thus our study demonstrates the primary role of GJ in rapid antidepressant efficacy of Yueju.